The Influence of Electrical Parameters on the Penetration of Tungsten into the SKD61 Workpiece Surface in PMEDM using Tungsten Carbide Powder - Le, Van Tao; Banh, Tien Long; Tran, Xuan Thai; Nguyen, Thi Hong Minh (Old Journal, 2017)
In the study, the authors studied the effect of the electrical current (I_p); the time-on discharge (T_on) on the penetration of tungsten into the surface of SKD61 steel at different concentrations of tungsten carbide powder used in powder mixed electrical discharge machining. The research has shown that the electrical current and the time-on discharge can impact greatly on the penetration of tungsten and the carbidation of the steel surface. In the mode of low electrical discharge, the penetration of tungsten into the surface and the carbidation of the surface is better than that of the mode of high electrical discharge.